The Use of Javanese Language with Banyumas Dialect in Family Environement for Children Ages 5-6 Years in Bojongsari Village, Bojongsari Disctrict, Purbalingga Regency - Fatmasari, Tiara; Eka Nugroho, R. Agustinus Arum (Jurusan PGPAUD FIP UNNES, 2018)
Children are the generation of local culture from previous generations who certainly love regional culture. One of the areas of the cultures that need to be preserved is the local language. Local language is also an area that reflect cultural heritage in its right. The use of Javanese language Banyumas dialect in the environment for a child's family is the local language preservation efforts from parents to children. The reality in the field of the use of the Javanese language with Banyumas dialect is now rarely used by parents of early childhood when communicating with children, especially in the family environment. Therefore, the purpose of this study is to analyze the use of the Banyumas dialect in the family environment for children age 5-6 years in Bojongsari Village, Bojongsari District, Purbalingga Regency. This research is a qualitative research, the researcher directly examine the source of data naturally and examine it as a key instrument. Data collection techniques use is observation, interviews, documentation, and triangulation. Data analysis techniques use the Miles and Huberman model. The results show that the Javanese language Banyumas dialect is still used in a family environment for children 5-6 years old. Besides that, Javanese language Banyumas dialect used as well as the everyday language among members of the family; parents with parents, parents with children, and children with children in hamlet 4, Bojongsari Village, Bojongsari District, Purbalingga Regency. Suggestions from the results of the study, which is for all family members to continue to preserve the local language (Javanese Banyumas dialect language) in the family environment by using the local language (Javanese Banyumas dialect), so that embedded love for local language from an early age.